EFEKTIVITAS METODE FUN LEARNING MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK USIA DINI KELOMPOK B DI TAMAN KANAK-KANAK AISYIYAH BUSTANUL ATHFAL KARANGAGUNG PALANG TUBAN TAHUN PELAJARAN 2023/2024 - Suharsono; Maftuhah; Dzul Zahrotun Nisa (STIT Muhammadiyah Paciran Lamongan, 2024)
This research is based on the obligation of Muslims to instill and teach Islamic religious education from an early age, but on the other hand, the situation of students who often feel bored and difficult to understand the material learned, especially in early childhood whose characteristics are still unstable and seem to be more engrossed in their own world and many teachers who still apply monotonous learning and less varied and boring learning. The Fun Learning method is one of the best alternative methods used in learning, especially in early childhood. The purpose of this researcher is to determine the effectiveness of the Fun learning method on Islamic Religious Education learning in early childhood with the type of qualitative research, data obtained by collection techniques through observation and interviews. The sample in this study is 20 students. The findings of this study show that the fun learning method for learning Islamic religious education in early childhood runs effectively. This can be seen from the process of learning management by teachers is carried out well, teachers master the material well because they can convey the material in a language that is easy for children to understand, The media used can support learning, the fun learning method used can make learning fun and learning takes place communicatively